Molar Pregnancy and Insitu Hysterectomy: A Case Report - Subedi, Hem Nath; Poudel, Sumita (International Journal of Silkroad Institute of Research and Training, 2024)
The gestational trophoblastic disease, with its most frequent representative, the hydatidiform mole, has a particular place in the obstetrical pathology being the only neoplasm linked to the fecundation process and because of its uncommon and sometimes unpredictable gravity. We present two patients with hydatidiform mole case one 50 yrs with molar pregnancy directly gone of total abdominal hysterectomy and second case 40 yrs previously suction evacuation done then gone for total abdominal hysterectomy. Ultrasonography for invaluable for the diagnosis and b hcg was the tools for diagnosis and follow up. Decrease of beta-hCG levels was reassuring in both cases. Contraception completed the follow-up plan for the young, fertile patient.